Handbook of research on IoT, digital transformation, and the future of global marketing - El-Gohary, Hatem, 1970-; Edwards, David, 1968-; Ben Mimoun, Mohamed Slim, 1974- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"This book offers an understanding of the different current digital age marketing trends with an aim to link industry with academia by providing useful insights on how to improve businesses ability in creating and maximizing customers' value and loyalty"--